Chemical composition and antifungal activity of essential oils and their combinations against Botrytis cinerea in strawberries - Oliveira Filho, Josemar Gonçalves de [UNESP]; da Cruz Silva, Guilherme; de Aguiar, Aline Cristina; Cipriano, Lavinia; de Azeredo, Henriette Monteiro Cordeiro; Bogusz Junior, Stanislau; Ferreira, Marcos David (Springer Nature, 2021)
Strawberry has a short postharvest shelf life, mainly because of the gray mold caused by Botrytis cinerea. The chemical composition and antifungal activities of essential oils from Mentha piperita, Cymbopogon martinii, Cinnamomum camphora, Mentha spicata, and their binary mixtures against B. cinerea were evaluated by different in vitro methods, and also in vivo in vapor-phase on inoculated strawberries. The major components present in M. piperita essential oil were menthol (45.37%), menthone (20.13%), isomenthone (16.94%), menthyl acetate (3.81%), pulegone (1.89%), α-terpinene (1.88%), isopulegol (1.83%), neoisomenthol (1.19%), and α-terpineol (1.08%), in C. martinii essential oil were geraniol (83.82%), geranyl acetate (7.49%), linalool (2.48%), and caryophyllene (1.33%), in C. camphora essential oil were linalool (98.39%), and M. spicata essential oil were carvone (61.71%), limonene (20.22%), 1,8-cineole (5%), sabinene (2.28%), cis-dihydrocarvone (1.63%), and α-thujene (1.4%). The highest antifungal activity in vitro was presented by M. spicata and C. martinii essential oils by the direct contact, vapor contact, spore germination, and micro-well dilution methods. In vivo, strawberries treated with the vapor of M. spicata and C. martinii essential oils showed a reduction in disease incidence and severity. At a 10% concentration, M. spicata and C. martinii showed a reduction of 100% and 83% in the disease incidence, respectively. Thus, the M. spicata and C. martinii essential oils may be potential alternatives for the control of B. cinerea in postharvest fresh strawberries.
Keywords: Gray mold Cymbopogon martinii; Mentha spicata; Minimal inhibitory concentration; Natural antimicrobials